Solid Dispersion Approaches for Clozapine Solubility Enhancement: A Comparative Review of Solvent Evaporation and Melt Fusion Methods - Pradnya Nitesh Valavi,; Yogesh.P. Sharma,; Dr.Sunil. K. Mahajan, (Asian Journal of Pharmaceutical Research and Development, 2026)
Clozapine, an antipsychotic belonging to the dibenzodiazepine family, continues to be the benchmark therapy for refractory schizophrenia even after being identified as having a difficult biopharmaceutics profile. The BCS Class II drug is highly permeable but poorly soluble in water (~0.2–0.5 mg/mL at physiological pH), which leads to poor oral bioavailability (27–50%) and high interpatient variability in pharmacokinetics. Solid dispersions are considered among the most potent techniques to deal with this issue through converting the drug from the crystalline form to the amorphous phase suspended in hydrophilic carrier matrices. This paper conducts a comparative study of two key solid dispersion approaches, namely solvent evaporation (spray drying and freeze drying) and melt fusion (hot melt extrusion and melt granulation), when applied to clozapine formulation. The physicochemical and biopharmaceutics characteristics of clozapine are thoroughly discussed regarding formulation design principles. Selection criteria for carriers, which include solvent solubility, glass transition temperature, miscibility indices (Flory-Huggins interaction parameter, χ), and thermal stability, are thoroughly analyzed. The mechanisms responsible for improving solubility, including amorphization, wetting enhancement, prevention of drug crystallization, and drug-polymer interactions, are examined with particular emphasis on current characterization methods such as differential scanning calorimetry, powder X-ray diffraction, Fourier transform infrared spectroscopy, solid-state nuclear magnetic resonance, and dissolution studies. Preclinical and formulation work from 2015 to 2026 is briefly reviewed in the context of achieving 4-10 fold increases in clozapine dissolution and bioavailability. Future directions concerning scale up, physical instability, residual solvents, and regulation, particularly the use of continuous manufacturing and artificial intelligence-based formulation, are explored.